Evaluation of patellar tendon mechanical properties and the preferred landing leg in elite jumping athletes - Gupta, A.; Allison, G.; Cook, J.; Purdam, C. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this investigation was to evaluate patellar tendon (PT) mechanical properties in healthy, elite jumping athletes and the association with their preferred landing leg. METHOD: Elite athletes (N=38) free of musculoskeletal pain were recruited from the Australian Institute of Sport, Australia. Subjects included 11 male volleyballers (MVB) (mean (SD) age (years), height (m) and weight (kg)) (17.5 (0.1), 2 (0.1) and 91.6 (8.9)), 13 male basketballers (MBB) (17.2 (1), 2 (0.1) and 87 (13)) and 14 female basketballers (FBB) (17 (0.8), 1.8 (0.1) and 78.1 (10.6)). Diagnostic ultrasound (US) (12MHz transducer, Nemio, Toshiba, Japan) was used to record the PT cross-sectional area. Ramped maximal voluntary isometric knee extension contraction (MVIC) at 90 degrees knee flexion was performed (KinCom dynamometer, Chattanooga, USA). Knee torque and PT length, from inferior pole of the patella to the tibial tuberosity, were determined at rest and 10% MVIC increments. PT force was calculated as knee extension torque divided by PT moment arm length, measured utilising a custom-made caliper (ICC = 0.7). PT mechanical properties (strain, stress, stiffness and elastic modulus) were calculated at 10% increments from 0 to 100% MVIC effort. T-tests were performed for inter-side and group comparisons. Sporting groups were stratified by landing leg as either left preferred landing leg (LPLL) or right preferred landing leg (RPLL). RESULTS: In MVB the left and right PT are less stiff for the LPLL group compared to the left and right PT of the RPLL group (p . 0.02) only at sub-maximal efforts in MVB. DISCUSSION: In volleyball, where there is a greater prevalence of jumpers knee than basketball (Lian O.B. et al, 2005), exposure to a sport-specific PT loading strategy may contribute to differences in PT mechanical properties based on the preferred landing leg. CONCLUSION: This preliminary investigation may demonstrate sport-specific PT loading strategy observed as a difference in PT stiffness based on the preferred landing leg.